The Role of Innovation in the Healthcare Supply Chain of Thailand - Fongtanakit, Ratchada; Somjai, Sudawan; Prasitdumrong, Amnaj; Jermsittiparsert, Kittisak (International Journal of Supply Chain Management, 2019)
This research aims at analyzing the influence of innovation on the performance of organizations with reference to healthcare industry. The influence on organizational performance by SC efficiency, supplier cooperation, innovation, and quality management practices (QM) has been shown by the research model. The structural equation modeling was used to test the hypothesis and proposed research model. The data was collected from about 243 hospitals. It has been supported by the results that there is positive association between SC innovation constructs and organizational performance. A significant influence is created by the innovative design of supply chain on QM practices, suppliers’ relation, and improvement of QM practices. The information was collected from a large sample of about 100 beds in the hospitals of Thailand. The sample size of hospitals may limit the result generalization. A useful information planning is provided by the study for healthcare sector. The research found that continuous improvements in innovation with the cooperation of supplier could result in the implementation of SC management successfully. This ultimately improves the performance of organization.